2023
DOI: 10.1111/jdv.19135
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of anti‐IL‐23 and anti‐IL‐17 after adalimumab failure in psoriatic patients

Abstract: BackgroundMany national guidelines at the European level recommend first‐line therapy based on the anti‐TNF‐alpha adalimumab for treatment of psoriasis and psoriatic arthritis, mainly for economic reasons. Consequently, patients being treated with newer IL‐17 and IL‐23 inhibitors underwent previous unsuccessful first‐line adalimumab‐based therapy.ObjectivesEvaluate the efficacy and safety of IL‐17 and IL‐23 inhibitors after treatment with adalimumab compared to adalimumab‐naive psoriatic patients.MethodsWe ret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 27 publications
2
8
0
Order By: Relevance
“…Dear Editor, We would like to answer the issues raised by Dr. Yu and Cheng-Chun Wei in their letter titled "Regarding Mastorino et al's 'Efficacy of anti-IL-23 and anti-IL-17 after adalimumab failure in psoriatic patients' 1 as authors of the discussed article. 2 About the first point of the letter, concerning the rapidity of action of IL-17 inhibitors compared to IL23 inhibitors and the supposedly higher drug survival of the latter, we agree with the authors regarding the lack of real-life studies on the subject. From our point of view, we have published some papers showing a not different survival among the same biologics class and possibly suggesting a higher survival of IL-23 inhibitors at indirect comparison.…”
supporting
confidence: 60%
See 1 more Smart Citation
“…Dear Editor, We would like to answer the issues raised by Dr. Yu and Cheng-Chun Wei in their letter titled "Regarding Mastorino et al's 'Efficacy of anti-IL-23 and anti-IL-17 after adalimumab failure in psoriatic patients' 1 as authors of the discussed article. 2 About the first point of the letter, concerning the rapidity of action of IL-17 inhibitors compared to IL23 inhibitors and the supposedly higher drug survival of the latter, we agree with the authors regarding the lack of real-life studies on the subject. From our point of view, we have published some papers showing a not different survival among the same biologics class and possibly suggesting a higher survival of IL-23 inhibitors at indirect comparison.…”
supporting
confidence: 60%
“…Regarding the prevention of joint involvement, some studies seem to observe this possibility in patients treated with guselkumab. 2 On the other hand, risankizumab and tildrakizumab proved effective in the management of skin involvement in both patients with psoriasis and psoriatic arthritis without significant differences. 6 Concerning the need for data on ethnic groups other than Caucasian, we totally agree with the authors' position; however, this necessarily falls within the limits of a real-life study conducted in a university hospital in Northern Italy.…”
mentioning
confidence: 99%
“…The high efficacy of these new biologics drives higher expectations and goals in the treatment of moderate‐to‐severe psoriasis 8 . Improvement of Psoriasis Area Severity Index by 90% (PASI90) or achievement of absolute PASI ≤ 3 until 16 weeks of treatment, achievement of Dermatology Life Quality Index (DLQI) of 0/1 until the same endpoints, safety, major drug survival (DS), and reduction of inflammatory progression are the current aims in the treatment of psoriasis 9,10 . Several randomized controlled trials (RCTs) have revealed the superiority of anti‐IL‐17 molecules ixekizumab and secukinumab compared to anti‐TNF alpha 11 .…”
Section: Introductionmentioning
confidence: 99%
“…Previous reports suggest that abnormal crosstalk between keratinocytes and immune cells, mediated by T cells, is an important threat in the etiopathogenesis of psoriasis. The IL-23/IL-17 axis is particularly recognized as a key contributor to the initiation and progression of psoriasis. , When stimulated by IL-23, T17 cell-produced cytokines trigger an inflammatory response in keratinocytes through the activation of the NF-κB signaling pathway. This is followed by an up-regulation of inflammatory products derived from keratinocytes, ultimately contributing to keratinocyte proliferation. , Apart from the immune factor, the antioxidant system acts as a defense mechanism against reactive oxygen species (ROS).…”
Section: Introductionmentioning
confidence: 99%
“…The IL-23/IL-17 axis is particularly recognized as a key contributor to the initiation and progression of psoriasis. 4,5 When stimulated by IL-23, T17 cell-produced cytokines trigger an inflammatory response in keratinocytes through the activation of the NF-κB signaling pathway. This is followed by an up-regulation of inflammatory products derived from keratinocytes, ultimately contributing to keratinocyte proliferation.…”
Section: Introductionmentioning
confidence: 99%